2021
DOI: 10.1037/xge0001022
|View full text |Cite
|
Sign up to set email alerts
|

Rules of order: Evidence for a novel influence on ordinal processing of numbers.

Abstract: Research on how people process numerical order carries implications for our theoretical understanding of what a number means and our practical understanding of the foundation upon which more sophisticated mathematics is built. Current thinking posits that ordinal processing of numbers is linked to repeated practice with the integer count list, but the mechanisms underlying this link remain unclear. For instance, in standard ordinal verification paradigms, participants more rapidly and accurately verify that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Reconceptualizing the reverse distance effect as a byproduct of this familiarity effect is, however, at odds with the view that nonconsecutive sequences are processed slower due to conflicting with an intuition that only count‐list sequences are correctly ordered (e.g., Gattas et al., 2021). From this perspective, non‐count‐list (i.e., nonconsecutive) sequences should always be processed slowly due to not matching the count‐list.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reconceptualizing the reverse distance effect as a byproduct of this familiarity effect is, however, at odds with the view that nonconsecutive sequences are processed slower due to conflicting with an intuition that only count‐list sequences are correctly ordered (e.g., Gattas et al., 2021). From this perspective, non‐count‐list (i.e., nonconsecutive) sequences should always be processed slowly due to not matching the count‐list.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is unknown whether these findings will generalize to double‐digit sequences. In fact, reverse distance effects have actually been found to be stronger in double‐digit sequences than in single‐digit sequences (e.g., Gattas et al., 2021; Lyons & Ansari, 2015). These findings are seemingly inconsistent with the familiarity perspective since one would perhaps expect the difference in familiarity between consecutive and nonconsecutive sequences to be lesser in double‐digit sequences than in single‐digit sequences; therefore, one may expect a weaker rather than stronger reverse distance effect in double‐digit sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One proposed alternative to the facilitation account stems from suggestions that young children may initially believe that “in order” refers only to sequences that directly match the count-list ( Gilmore & Batchelor, 2021 ; Hutchison et al, 2022 ). Therefore, it has been argued that the reverse distance effect might actually result from the processing of non-consecutive sequences being impeded due to conflicting with this intuition, rather than from consecutive sequences being facilitated by memory retrieval ( Gattas et al, 2021 ). However, although both the facilitation and count-list interpretations of the reverse distance effect seem plausible, there has been limited direct comparison between them ( Devlin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…To test whether people are predisposed to consider non-consecutive sequences as not in order, Gattas et al (2021) varied the instructions given to participants taking an order judgement task. Surprisingly, they found that adult participants were faster at classifying non-consecutive sequences as not in order than they were at classifying them as in order.…”
Section: Introductionmentioning
confidence: 99%